15-Minute City and Elderly People: Thinking about Healthy Cities - Ulloa León, Felipe.; Correa Parra, Juan Pablo.; Vergara Perucich, José Francisco.; Cancino Contreras, Francisca Lucía.; Aguirre Núñez, Carlos. (MPDI, 2023)
Considering the global scenario of population aging, which countries such as Chile are going through, the social problems that it means in terms of viability and quality of life for the elderly are increasing and are a cause for concern. For this reason, this study summarizes the results of investigating the accessibility of services and recreational spaces under the parameters of a “15-minute city” for the elderly people in the city of Santiago de Chile. The investigation employed a multivariate geostatistical analysis with a quantitative approach and was developed on a census block scale to test some of the principles of the 15-min city along with the principles on active aging of the elderly. The results are surprising, show a good territorial coverage for the study area and open the possibility of Santiago becoming a 15-min city for older adults. However, there are still several challenges in terms of public policies, from mental and physical health to the design of public spaces, which are fundamental to think about for cities of the future
Keywords: 15-min city; Elderly people; Thinking about Healthy Cities